2020
DOI: 10.1136/bmjpo-2020-000884
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of newly diagnosed type 1 diabetes in children and young people during COVID-19: a national UK survey

Abstract: In the UK, there have been reports of significant reductions in paediatric emergency attendances and visits to the general practitioners due to COVID-19. A national survey undertaken by the UK Association of Children’s Diabetes Clinicians found that the proportion of new-onset type 1 diabetes (T1D) presenting with diabetes ketoacidosis (DKA) during this COVID-19 pandemic was higher than previously reported, and there has been an increase in presentation of severe DKA at diagnosis in children and young people u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 4 publications
(3 reference statements)
5
42
0
Order By: Relevance
“…This was evidenced by a lower pH at diagnosis, a higher presenting HbA 1c , and a greater risk of developing DKA and severe DKA. These observations are consistent with other reports documenting the higher rates of DKA in both paediatric and adult patient populations during the first months of the pandemic 7–10,13,14 . Pre‐pandemic, younger children presented more severely compared to older children, and this may relate to the known difficulty with recognizing diabetes symptoms in this age group 15 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was evidenced by a lower pH at diagnosis, a higher presenting HbA 1c , and a greater risk of developing DKA and severe DKA. These observations are consistent with other reports documenting the higher rates of DKA in both paediatric and adult patient populations during the first months of the pandemic 7–10,13,14 . Pre‐pandemic, younger children presented more severely compared to older children, and this may relate to the known difficulty with recognizing diabetes symptoms in this age group 15 .…”
Section: Discussionsupporting
confidence: 92%
“…The diagnostic accuracy and availability of defined clinical and biochemical end points permits detailed investigation of the effect of the pandemic on childhood onset type 1 diabetes. Reports show an unusually high proportion of children and young people presenting in diabetic ketoacidosis (DKA) during the pandemic 7–10 . In a nationwide survey of paediatric diabetes centres in the United Kingdom, delayed presentation was noted in 20% of children with newly diagnosed type 1 diabetes 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The increased incidence of severe DKA amongst patients diagnosed post-lockdown, whilst not significant, is a potential concern. This finding is consistent with the Italian data and with other units in the UK 12,17 . It initially appears to be counter-intuitive when one takes into account the reduction in the TDI and PI post-lockdown.…”
Section: Discussionsupporting
confidence: 93%
“…Similar anxieties had been expressed related to delayed presentation of patients with T1DM. 17 One survey of diabetes units in the UK reported that 20% of children and young people diagnosed with T1DM between 1 March and 30 June 2020 had had a delayed presentation. Reasons for this included fear of contracting SARS-CoV-2 as well as limited access to GP services.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, another study conducted in Italy between February 20 and April 14 in 2019 and 2020 found no difference in DKA incidence and new-onset T1DM diagnosis; however, an increase in DKA severity was observed ( 10 ). A survey from 88 diabetes centers in the UK between March 1, 2020, and June 30, 2020, showed an increase in the incidence and severity of DKA at diagnosis, and about 20% of the centers have attributed this to delayed presentation, while the incidence of new-onset T1DM diagnosis remained the same ( 12 ).…”
Section: Discussionmentioning
confidence: 99%